The Anopheles Culicifacies Species Complex in Relation to Malaria Transmission in Sri Lanka - Surendran, S.N. (Faculty of Science, University of Colombo, 2005)
Anopheles culicifacies Giles sensu lato (Diptera: Culicidae) is the predominant vector of malaria in Sri Lanka. Until recently, only sibling species B was reported to be present in Sri Lanka. The conundrum was that species B was reportedly a poor vector of malaria in India. The present study resolves this issue by demonstrating for the first time that what was described as species B in Sri Lanka is really a mixture of two species, viz. B and E, that are also apparently present in Rameshwaram Island, India. Species B and E share the same polytene chromosome configuration. However they differ in that the mitotic Y-chromosome is acrocentric in species B and submetacentric in species E. ...